Experimental and numerical study on the laminar burning velocities of n-decane/toluene/air mixtures at elevated temperatures. (15th August 2022) - Xie, Shengrong; Li, Xing; Li, Tao; Huo, Jiepeng; Wang, Junxiong; Wang, Chenguang; Wang, Xiaohan
Highlights: The LBVs of n-decnae/toluene/air mixtures were measured using EHDC method. The chemical, thermal and diffusion effects of toluene blending were analyzed. The temperature compensation method was used in the numerical study. Abstract: The laminar burning velocities (LBVs) of n-decane/toluene/air mixtures were measured at elevated temperatures using externally heated diverging channel (EHDC) method. The effects of initial temperature (up to 650 K), toluene blending ratio ( R C7H8 = 0 to 1.0 by liquid volume) and equivalence ratio ( ϕ = 0.6 to 1.4) on the LBVs of n-decane/toluene/air mixtures have been investigated. Numerical computation with a detailed reaction mechanism was used to further analyze the effects of potential interactions between n-decane and toluene. It was observed that the LBVs of n-decane/toluene/air mixtures increase with the increase of initial temperature, while the LBVs decrease with the increase of toluene blending ratio. The effects of toluene on the LBVs through chemical reactions, heat and mass transfer were analyzed in detail. Moreover, the temperature compensation method, which separates the effect of adiabatic flame temperature and contribution from chemical and disunion, was used in analysis. The effects of the toluene blending on the LBV is mainly attributed to chemical term, and the thermal effect have a second order importance. The reaction pathways and sensitivity analysis show that the LBVs of stoichiometric mixtures is less sensitive to kinetic coupling. The distinct flame propagation properties of the n-decane/toluene blended fuels are determined by the distributions of reaction rates of the crucial intermediate species and radicals.